Reducing the risk of suicidal behaviors in medical graduate students: exploration of student-supervisor relationship and subjective family socioeconomic status - Wu, Yan; Qu, Zheng; Tang, Wanjie; Zheng, Yunhao; Xiong, Xin; Ye, Zheng; Li, Zhenlin (Frontiers in Psychiatry, 2024)
Objective This study aimed to investigate the association between the risk of suicidal behaviors and student-supervisor relationships and subjective family socioeconomic status (SFSS) in medical graduate students, and to propose preventive strategies to reduce the suicidal risk among medical graduate students. Materials and methods A total of 1,310 validated questionnaires were collected from medical graduate students, which included demographic information, study programs, the Suicidal Behaviors Questionnaire-Revised (SBQ-R) questionnaire, the Leader-Member Exchange 7 (LMX-7) questionnaire, and SFSS by MacArthur Scale. Multiple regression analysis was employed to examine the associations between variables and adjust for confounders. A moderation analysis, containing simple slope analysis and Johnson-Neyman interval plots were used to analyze the moderating effect of the SFSS in the association of SBQ-R and LMX-7 scores. Results A total of 88 participants (6.7%) were at risk of suicidal behaviors. In the high-quality student-supervisor relationship group (LMX-7 score ≥ 25), SFSS was significantly higher than in the low- and moderate-quality relationship group (p=0.002). The median SBQ-R score and proportion of suicide risk was significantly lower (p<0.001) in the high-quality student-supervisor relationship group. Multiple regression analysis indicated LMX-7 scores (β=-0.098, 95% CI [-0.118, -0.077], p<0.001) and SFSS (β=-0.073, 95% CI [-0.127, -0.019], p=0.008) were significantly negatively associated with SBQ-R, whereas the interaction term of SFSS with LMX-7 (β=0.018, 95% CI [0.007, 0.029], p=0.001) showed a significant positive association with SBQ-R. The Johnson-Neyman interval showed a significant association between LMX-7 and SBQ-R scores only when SFSS was less than 7.82 (p<0.05). Conclusion The risk of suicidal behaviors was associated with student-supervisor relationships and SFSS among medical graduate students. Poor relationships with supervisor were associated with an elevated risk of suicidality, and SFSS moderated this association. Educators should pay increased attention to the suicidal risk of medical graduate students with poor supervisor relationships, especially those from families with low SFSS, and provide timely preventive strategies.